2015
DOI: 10.1111/all.12777
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to GOS/inulin mixture prevents food allergies and promotes tolerance in offspring in mice

Abstract: The treatment of pregnant and lactating mice with nondigestible GOS/inulin prebiotics promotes a long-term protective effect against food allergies in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Carbohydrates that are indigestible for host enzymes, such as dietary fiber, can be fermented by the gut microbiota, which exerts a prebiotic effect that stimulates the growth of beneficial strains and inhibits colonization by pathogenic bacteria. Supplementation of maternal diet with galacto-oligosaccharides and inulin during pregnancy and breastfeeding has shown an indirect effect on offspring, giving rise to an increased proportion of Lactobacillus species and Clostridium leptum and decreased proportion of Clostridium coccoides and promoting immune tolerance to wheat gliadin in offspring [113]. In addition, bacterial metabolic products including short chain fatty acids (SCFAs) have been shown to directly regulate mucosal immune function and the intestinal barrier [114].…”
Section: Role Of Microbiota and Dietmentioning
confidence: 99%
“…Carbohydrates that are indigestible for host enzymes, such as dietary fiber, can be fermented by the gut microbiota, which exerts a prebiotic effect that stimulates the growth of beneficial strains and inhibits colonization by pathogenic bacteria. Supplementation of maternal diet with galacto-oligosaccharides and inulin during pregnancy and breastfeeding has shown an indirect effect on offspring, giving rise to an increased proportion of Lactobacillus species and Clostridium leptum and decreased proportion of Clostridium coccoides and promoting immune tolerance to wheat gliadin in offspring [113]. In addition, bacterial metabolic products including short chain fatty acids (SCFAs) have been shown to directly regulate mucosal immune function and the intestinal barrier [114].…”
Section: Role Of Microbiota and Dietmentioning
confidence: 99%
“…In humans, the effects of maternal intake of prebiotics on neurodevelopment have not been well studied, and there is uncertainty about their effects on allergy risk [60, 61]. Galacto-oligosaccharide (GOS) and inulin administration to pregnant mice modulated the gut microbiota and prevented immune activation and intestinal permeability in the offspring [62]. Moreover, it has recently been shown that the addition of inulin to a mouse maternal high-fat diet abrogated the negative metabolic effect of the high-fat diet on offspring [63].…”
Section: External Challenges To Maternal Microbiota Dynamicsmentioning
confidence: 99%
“…Thus, several studies have provided evidence to support that supplementing with prebiotics and probiotics, specifically during pregnancy, modifies the methylation status of DNA, particularly of obesity promoters and genes related to weight gain in mothers and their infants [91,92]. Some examples of maternal prebiotic during pregnancy associated with programming offspring health, in animal models, are short-chain fructo-oligosaccharides that improve gut defense and immune response [93], galactooligosaccharides and inulin mixture that prevent food allergies [94] and oligofructose that decreases the risk of obesity [95]. Vahamiko, Laiho [96] carried out a pilot study that aimed to find out whether the administration of probiotic supplements during pregnancy might change DNA and the methylation status of obesity promoters and the genes related to weight gain in mothers and their children.…”
Section: Gut Microbiota and Metabolic Programmingmentioning
confidence: 99%